Digital Humanities in European Research Libraries: Beyond Offering Digital Collections - Wilms, Lotte (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Libraries are increasingly becoming involved in digital humanities research beyond the offering of digital collections. This article examines how libraries in Europe deal with this shift in activities and how they compare with libraries in other parts of the world. This article builds on the results of surveys conducted in Australia, New Zealand, Hong Kong, the United States and the United Kingdom, and compares them with a survey conducted in Europe. We found that European libraries are mostly active in research supporting activities, such as digitisation and storage, while US libraries often include analysis in their activities. Funding comes from the library’s main budget and non-structural funding in a variety of forms. Staff working in DH roles has a diverse range of titles, with various forms of librarians being the most used. Analytical staff such as GIS specialists are only found in the US survey. All surveyed libraries agree that the biggest skill gap amongst their staff is in technical skills. When looking towards the future, European libraries see the role of digital humanities (or digital scholarship) within the library grow and are making plans to facilitate this change within their organisation by positioning themselves as an attractive research partner, by opening and increasing their digital collections and by improving the internal workings of the library.